Redefining the spectrum of fistula-associated malignancy in Crohn’s disease: a rare case of colonic adenocarcinoma arising from a perianal fistula - Roche, Shruti N.; Hendy, Peter J.; Bhutada, Ekta; Ford, Alexis (International Surgery Journal, 2026)
Crohn’s disease (CD) is a chronic, relapsing, and progressive disease characterised by transmural inflammation affecting any segment of the gastrointestinal tract. Perianal fistulising CD (PFCD) affects approximately 20% of CD patients and is associated with a more aggressive disease course and reduced quality of life than those without fistulising disease. While the association between luminal colorectal cancer and CD has been well-established, PFCD-associated fistula cancers is a rarer entity. Existing literature is comprised mostly of case reports and case series, thus guidelines for detection and management of these cancers are scarce. Current diagnostic techniques display major shortfalls, necessitating the adoption of a multimodal, multidisciplinary approach. Further research is needed into its true incidence, pathophysiology and demographics, as well as the efficacy of and enhancing current diagnostic techniques. We present a case of a young female who developed an adenocarcinoma within a chronic perianal fistula.